ENHANCING BUSINESS PERFORMANCE OF CV IDEAS INDONESIA - Dwi Robby Prasetyo; Ketut Sadhunata Wisnukepakisan; Galih Bagus Priadi; Dhea Audria; Akhmad Syukra; Jerome C Tiberi (AIBPM Publisher, 2018)
IDEAS are an acronym for Innovation, Design, Engineering, and Art & Science. We have collaborated with the principle that a problem can be solved with an integrated solution. IDEAS were initiated in 2012 in Bandung. Starting with some disciplines such as Architecture, Economics, Design, Microbiology, & Agribusiness. With this diversity we can explore solution with various disciple. Our focus is on developing a sustainable lifestyle.